ANALISIS KESADARAN LINGKUNGAN MASYARAKAT DESA MATANG TEUNGOH, KECAMATAN COT GIREK, ACEH UTARA - Lestari, Dewi; Sari, Nirmala (Jurnal Samudra Geografi, 2024)
Cot Girek District is a district in North Aceh Regency, Aceh Province, Indonesia. It has a distinctive historical and cultural background, as well as considerable natural and economic potential. Aceh in general has a long history as one of the centers of Islamic civilization in Indonesia, Cot Girek District is also inseparable from the influence of strong Islamic culture and history. Matang Teungoh Village is a small village located in the heart of Indonesia, known for its expanse of green scenery and rich biodiversity. However, in recent years, the village has faced significant environmental hygiene problems, efforts made by local community members are to organize clean-up activities and educate the community on the importance of preserving the environment. this research uses qualitative methods (field research), qualitative research is a type of research whose findings are not obtained through statistical procedures or other forms of calculation. Qualitative methods are observation, interview, or document review. This research examines forms, activities, characteristics, changes, relationships, similarities, and differences with other phenomena.